Analysis and design of information systems news portal citizen journalism Sumba-Indonesia as local content promotion media - Jefonses Yarsian Pote (Universitas Ahmad Dahlan, 2018)
Citizen journalism is a journalistic activity undertaken by a person or group. So far, information on the potential of the Sumba Island has not been evenly distributed because there is unequal information on the Sumbanese community and information on potential in eastern Sumba. The purpose of this research is to provide media for the citizens of Sumba in providing any information about local content in Sumba Island such as information on agriculture, plantation, forestry, tourism, cultural information, social information, political information, law, and human rights. The methodology used to build this system is the Waterfall Model. This model is an approach to software development, with several stages, namely: System Engineering, Analysis, Design, Encoding, Testing, and Maintenance. The development concept used is Model-View-Controller or MVC is a method to create an application with separate data (see) and the corresponding way (Controller). In the implementation of framework in the application of website-based architecture MVC. MVC is developing a major component-based application that builds an application such as data manipulation, user interface, and parts that become controls in a web application.